Manajemen Strategis Kesiapsiagaan Nasional: Diplomasi Hedging Indonesia: Strategic Management of National Preparedness: Indonesia's Hedging Diplomacy - Tarigan, Benny Surya Abdi; Suryana, R.E.; Risdhianto, Agung (DAS Institute, 2026)
Indonesia's defense strategy faces unprecedented complexity in balancing military modernization, non-traditional security threats, and regional great power competition. This article examines how national preparedness (Kesiapsiagaan Nasional) can be effectively implemented through defense diplomacy, based on Indonesia's constitutional framework and strategic principles. Referencing a doctrinal analysis of Sishankamrata (Total People's Defense and Security System), official policy documents, and comparative regional security mechanisms, this study identifies institutional mechanisms, strategic principles, and implementation challenges in integrating defense diplomacy with national preparedness. The research shows that Indonesia's hedging strategy, operationalized through multilateral confidence-building measures and multilevel defense cooperation, provides a viable framework for managing security risks while maintaining strategic autonomy. However, civil-military coordination gaps, resource constraints, and institutional ambiguities related to the “Digital Sovereignty Doctrine” remain significant obstacles. The article concludes with specific policy recommendations to strengthen interagency coordination, capacity building, and the institutionalization of defense diplomacy as comprehensive tools for national security. These findings contribute to the understanding of how middle powers navigate contemporary security challenges through strategic autonomy and multilateral engagement in a competitive regional environment.